2021
DOI: 10.3389/fphar.2021.730461
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C19 Genotyping May Provide a Better Treatment Strategy when Administering Escitalopram in Chinese Population

Abstract: Depression disorder is one of the most serious mental illnesses in the world. Escitalopram is the essential first-line medication for depression disorder. It is the substrate of hepatic cytochrome P450 (CYP) enzyme CYP2C19 with high polymorphism. The effect of CYP2C19 on pharmacokinetics and pharmacodynamics on Caucasian population has been studied. The Clinical Pharmacogenetics Implementation Consortium Guideline provides dosing recommendations for escitalopram on CYP2C19 genotypes on the basis of the studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Arbidol is mainly metabolized by the CYP3A4 isoenzyme in humans, so theoretically inducers or inhibitors of CYP3A4 will affect the metabolism of arbidol. LPV/r as protease inhibitors had a significant interaction with arbidol, which increased the C max and AUC (0-∞) of both drugs ( Huang et al, 2021 ). In this experiment, napabucasin is found to be a bioactivator of quinone oxidoreductase 1 that generates reactive oxygen species ( Chang et al, 2019 ; Froeling et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arbidol is mainly metabolized by the CYP3A4 isoenzyme in humans, so theoretically inducers or inhibitors of CYP3A4 will affect the metabolism of arbidol. LPV/r as protease inhibitors had a significant interaction with arbidol, which increased the C max and AUC (0-∞) of both drugs ( Huang et al, 2021 ). In this experiment, napabucasin is found to be a bioactivator of quinone oxidoreductase 1 that generates reactive oxygen species ( Chang et al, 2019 ; Froeling et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the combination of lopinavir/ritonavir (LPV/r) and arbidol will be a risk factor for liver injury in patients with non-critical COVID-19 ( Cai et al, 2020 ). Studies reported that when LPV/r was combined with arbidol, the C max of arbidol was increased and the AUC (0-∞) of arbidol was significantly increased from 705.6 to 1250.3 ng/mL*h ( Huang et al, 2021 ). In addition, pharmacokinetic and metabolic differences caused by administration of arbidol were found in male and female rats.…”
Section: Introductionmentioning
confidence: 99%
“…5,[8][9][10] However, only 50%-60% of patients respond to SCIT, 11 this may be partially ascribed to inter-individual (IIV) differences in metabolic capacity, influenced by genetic variability in drug-metabolizing enzymes, specifically the hepatic cytochrome P450 (CYP) system. [12][13][14][15] Consequently, using a one-size-fits-all approach for all patients could lead to treatment failure and unexpected adverse drug reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Escitalopram is primarily metabolized in the liver by cytochrome P (CYP)450, particularly CYP2C19, which is a highly polymorphic enzyme that causes interindividual pharmacokinetic differences ( Rao, 2007 ; Pastoor and Gobburu, 2014 ), and is excreted mainly through the kidneys. The effect of age ( Dolder et al, 2010 ; Yang and Scott, 2010 ), gender ( Montejo et al, 2015 ), smoking ( Oliveira et al, 2017 ; Scherf-Clavel et al, 2019 ), CYP2C19 phenotype ( Huang et al, 2021 ), hepatic impairment ( Areberg et al, 2006 ), and renal impairment ( Dolder et al, 2010 ) on the pharmacokinetics of escitalopram have been investigated. The findings of these studies were instrumental in developing specific dosing recommendations for escitalopram for specific populations ( Hicks et al, 2015 ; Brouwer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%